Living As Citizen In Smart City - Lestari, Lara Ayu; Angreni, Dyah Kuntorini Dwi; Zana, Iqbal Saputra; Andreastuti, Desie; Bato, Bulan Erika; Perwitasari, Dyah Rahayuning (Faculty of Social Science, Universitas Negeri Padang, 2025)
The idea of smart cities has gained traction recently. It has attracted much attention from administrators, legislators, urban planners, and others in response to the complicated problems caused by unparalleled urbanization. However, public participation or citizen engagement is essential in the smart city concept to achieve the goals optimally. This research will primarily focus on several methodologically crafted problem sets to produce thorough analytical results. They ask how the notion of